Acute Ischemic Stroke : Medical, Endovascular, and Surgical Techniques - Park, Jaechan (Springer Singapore : Imprint: Springer, 2017)
This book approaches the topic of management of acute ischemic stroke in an interdisciplinary manner, explaining how best to utilize the methods currently available for medical, surgical, and endovascular care. After an opening section on basics such as pathophysiology, radiological assessment, and pathology, comprehensive and up-to-date information is provided on each of the available therapies, techniques, and practices. Special attention is paid to recent advances in neurointerventional and neurosurgical procedures, with clear description of important technical details.The book includes plentiful high-quality case illustrations and a wealth of practical information that will prove of value in emergency rooms, angiography suites, operating rooms, and intensive care units. It will aid not only neurologists, neurointerventionists, and neurosurgeons, but also all others who are involved in the management of acute ischemic stroke, from radiologists and emergency physicians to healthcare providers.
Keywords: Medicine.; Radiology.; Critical care medicine.; Neurology.; Neurosurgery.; elektronické knihy; electronic books